Transitional studies - Schulte, P A; Perera, F P (IARC scientific publications, 1997)
Transitional studies are studies using biological markers that bridge the gap between laboratory experiments and population-based epidemiology. The goal of these studies is to characterize and validate biomarkers and to assess the following: intra- and inter-subject variability; the feasibility of marker use in field conditions; confounding and effect-modifying factors for the marker; and mechanisms reflected by the biomarker. Another goal is to optimize the conditions for the use of biomarkers. Transitional studies involving biomarkers of exposure or effect are distinguished from etiological studies because the biomarker is generally the outcome or dependent variable. Despite this difference, transitional studies can be epidemiological studies, but they may also include laboratory studies to assess reliability (and accuracy) and to identify parameters for collecting, processing and storing biological specimens prior to assay. Generally, transitional studies involve healthy people, patients or workers with specific exposures. At some point in the validation of a biomarker the line between transitional and etiological studies becomes blurred. None the less, it is useful to identify transitional studies as a distinct set of efforts to validate and characterize biomarkers. Transitional studies can be divided into three functional categories: developmental, characterization and applied studies.